Mobilization of the blaKPC-14 gene among heterogenous plasmids in extensively drug-resistant hypervirulent Klebsiella pneumoniae - Wang, Lin; Shen, Weiyi; Cai, Jiachang (Frontiers in Microbiology, 2023)
Herein, we reported the evolution of a conjugative mosaic plasmid encoding the blaKPC-14 gene via mobile elements in carbapenem-resistant Klebsiella pneumoniae (CRKP) isolated from two patients in intensive care units. Three CRKP displayed resistance or reduced susceptibility to ceftazidime/avibactam, colistin, and tigecycline. Single-nucleotide polymorphism (SNP) analysis demonstrated the close phylogenetic distance between these strains. A highly similar IncFII/IncR plasmid encoding blaKPC-14 was shared by three CRKP, with blaKPC-14 located in an NTEKPC-Ib element with the core region of ISKpn27-blaKPC-14-ISKpn6. This structure containing blaKPC-14 was also observed in another tet(A)-carrying plasmid that belonged to an unknown Inc-type in two out of three isolates. The horizontal transferability of these integrated plasmids to Escherichia coli EC600 was confirmed by the cotransmission of tet(A) and blaKPC-14 genes, but the single transfer of blaKPC-14 on the IncFII/IncR plasmid failed. Three CRKP expressed yersiniabactin and carried a hypervirulence plasmid encoding rmpA2 and aerobactin-related genes, and were thus classified as carbapenem-resistant hypervirulent K. pneumoniae (hvKP). In conclusion, this study identified two structurally different blaKPC-14-carrying plasmids in extensively drug-resistant hvKP. The blaKPC-14 gene is prone to integrate into other conjugative plasmids via the NTEKPC-Ib element, further facilitating the spread of ceftazidime/avibactam resistance and alerting the need for active surveillance of blaKPC-14.